FACTORS OF REGIONAL ECONOMIC SECURITY - L. S. Arkhipova; I. V. Gorokhova (Вестник Российского экономического университета имени Г. В. Плеханова)
During the last two decades The Russian Federation experienced a serious external pressure on the part of western countries, including the impact of unfair competition on global commodity markets and sectional costs. At the same time global geo-political space is undergoing changes too. Principle risks and threats to national and regional economic security, which kept arising in the previous years in many regions of the country, are becoming the most topical. Our home market demonstrates different dynamics of its development, which is characterized by low economic growth, regional disproportions in social and economic development, shortage of investment. Positive indicators include relative sustainability of economy, surplus of regional budgets, success of certain entities of the country in attaining strategic goals, a high level of openness of Federation entities’ economy. In this context identification of key risks and threats to regional economic security acquires special importance, designing approaches to their minimization and elimination is also essential. Unfortunately, there is no universal approach to their elimination in the global practice, however, it is possible to lower their impact on social and economic sphere. The authors analyzed a number of key factors influencing economic security in regions. Two large macro-regions of Russia, i. e. the Central and the Privolzhskiy Federal districts were investigated. Using their example entities, which are included in these districts, were typified by dynamics of certain indicators. It showed serious differentiation, the trends of investment shortage dominates in the majority of regions. In both districts, mentioned above the share ofinvestment into fixed capital in gross regional product and returns on assets ratio decreased. Only the Kaluga region as an entity of the Central Federal district shows positive dynamics. Specific weight of shipped innovation products in the total volume of industrial output (indicator) demonstrates the level of economic security of the area in view of its competitiveness. The authors showed that the number of regions with growing dynamics of innovation products output is prevailing. Disproportions in key indicators of regional economic security were found. Positive factors of its growth, such as availability of serious potential of innovation economy development were identified.